2022
DOI: 10.3390/ijms23137484
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Skin–Brain Axis: New Vistas Using Mouse Models

Abstract: Inflammatory diseases of the skin, including atopic dermatitis and psoriasis, have gained increasing attention with rising incidences in developed countries over the past decades. While bodily properties, such as immunological responses of the skin, have been described in some detail, interactions with the brain via different routes are less well studied. The suggested routes of the skin–brain axis comprise the immune system, HPA axis, and the peripheral and central nervous system, including microglia response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 123 publications
0
4
0
Order By: Relevance
“…[42] The "skin-brain axis" plays a role in the interplay between skin disorders and psychiatric disorders through the regulation of peripheral nervous system pathways, the hypothalamic-pituitary-adrenal axis, the sympathetic-adrenomedullary system, and the immune system. [43][44][45] Therefore, more experimental studies are needed to elucidate the specific mechanisms underlying the causal relationship between skin and psychiatric disorders to support our findings.…”
Section: Discussionmentioning
confidence: 73%
“…[42] The "skin-brain axis" plays a role in the interplay between skin disorders and psychiatric disorders through the regulation of peripheral nervous system pathways, the hypothalamic-pituitary-adrenal axis, the sympathetic-adrenomedullary system, and the immune system. [43][44][45] Therefore, more experimental studies are needed to elucidate the specific mechanisms underlying the causal relationship between skin and psychiatric disorders to support our findings.…”
Section: Discussionmentioning
confidence: 73%
“…48 In the skin-brain axis, psoriasis as a chronic stress activates the hypothalamic-pituitary-adrenal (HPA) axis, which can control the immune system via neuroendocrine factors and the autonomous nervous system. 49 Therefore, this study might provide new insights into psoriasis and novel ideas for its treatment and diagnosis. To this end, the limitations of this study should be overcome in the future, including the verification of large-scale clinical samples and the mechanisms by which ADAM23 is involved in the pathogenesis of psoriasis.…”
Section: Discussionmentioning
confidence: 96%
“… 48 In the skin–brain axis, psoriasis as a chronic stress activates the hypothalamic–pituitary–adrenal (HPA) axis, which can control the immune system via neuroendocrine factors and the autonomous nervous system. 49 …”
Section: Discussionmentioning
confidence: 99%
“…Further studies found that patients with psoriasis who were female, young, had a young age of onset, and had skin lesions in sensitive or visible areas were at increased risk of psychosocial disorders [ 49 ]. While scholars previously attributed the psychological comorbidities of psoriasis to the psychological stigma and reduced quality of life caused by skin damage, subsequent studies have found overlapping genetic loci and cross-cutting inflammatory response pathways between the two [ 50 , 51 ]. Additionally, biologics have been shown to reduce the risk of depression in patients with psoriasis, possibly due to a reduction in systemic inflammation [ 52 ].…”
Section: Discussionmentioning
confidence: 99%